Steel slag-based porous ceramic composite phase change material and preparation method thereof
By using industrial solid waste such as steel slag and fly ash and biomass waste, combined with foaming agent pore formation method and sacrificial template method, the problems of high packaging cost and low resource utilization rate of composite phase change materials are solved. , achieving efficient load phase change materials and reducing environmental hazards.
Patent Information
- Application Number
- CN202411501470.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-01-07
AI Technical Summary
In the prior art, the packaging cost of composite phase change materials is high, and corrosion and leakage are prone to occur. The resource utilization rate of industrial solid waste, biomass waste and plastic waste is low, which affects the application of thermal energy storage.
Porous ceramics are prepared by using industrial solid waste, biomass waste and plastic waste such as steel slag and fly ash as raw materials, and the pore structure is improved by combining the volatile components in the steel slag. and the loading rate of phase change materials, the process is simplified using vacuum adsorption impregnation.
The prepared steel slag-based porous ceramic has high porosity, high hardness and excellent stability, and can efficiently load phase change materials, reduce dependence on natural ore, improve resource utilization, reduce environmental hazards, and significantly reduce The cost.
Smart Images

Figure CN119263882A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of phase change material preparation, and in particular to a steel slag-based porous ceramic composite phase change material and a preparation method thereof. Background Art
[0002] The energy output of new energy sources such as solar energy and wind energy is very unstable. In order to ensure uninterrupted energy supply throughout the day, a huge energy storage system is needed to allocate the energy supply. Electric energy storage is expensive, and hydropower storage is easily affected by geographical factors. Latent heat storage has the advantages of low cost, high energy storage density, constant phase change temperature, and no geographical restrictions. It has broad application prospects in thermal energy storage technology. However, phase change materials have problems such as low thermal conductivity, easy leakage, and high supercooling, which seriously affect their application in thermal energy storage. Encapsulating phase change materials in porous carriers to prepare shape-stable phase change materials is an effective way to solve the above problems. Common porous carriers include expanded graphite, metal organic frameworks, biomass materials and porous ceramics. Among them, porous ceramics have the characteristics of high temperature resistance, corrosion resistance, high porosity, and stable structure.
[0003] Industrial solid waste such as steel slag contains a large amount of metal oxides and silicon dioxide, which can be mixed with materials such as kaolin to prepare steel slag-based porous ceramics. Polyurethane foam has a good pore structure. Using the sacrificial template method, polyurethane foam is used as a template to prepare steel slag-based porous ceramics with good pore structure and hardness. In addition, the prepared steel slag-based porous ceramics have excellent stability, corrosion resistance and high temperature resistance, and can load a variety of phase change materials such as organic / inorganic, high temperature / low temperature, etc. The annual output of industrial solid waste in my country is huge, and its large accumulation will occupy a lot of land resources and endanger the safety of the ecological environment. The application of industrial solid waste in thermal energy storage can effectively improve the resource utilization rate of solid waste and reduce its harm to the environment.
[0004] Chinese invention patent CN202211273446.2 discloses a ceramic-based molten salt composite phase change heat storage material and a preparation method thereof. The process mainly uses volatile components to form pores. The prepared porous ceramic has low porosity, limited load rate on phase change materials, and limited latent heat value of the prepared composite phase change. Chinese invention patent application CN202410672869.4 discloses a composite phase change material, a phase change thermostatic lightweight ceramic brick and a preparation method thereof. The process mainly uses sodium carbonate and / or sodium bicarbonate as pore-forming agents, and the porosity is low. In the present invention, a variety of pore-forming technologies are used. In addition to using volatile components in steel slag for pore-forming, a foaming agent pore-forming method and a sacrificial template method are also used. Using porous materials such as polyurethane foam as templates, three-dimensional porous ceramics can be obtained. The foaming agent can further generate uniform pores on the skeleton of the three-dimensional porous ceramic. The steel slag-based porous ceramics prepared by combining a variety of pore-forming technologies have a richer pore structure. In the sacrificial template method, the present invention adopts a partial filling strategy, which can further improve the pore structure of the porous ceramic and the loading rate of the phase change material compared to the conventional complete filling strategy.
[0005] Chinese invention patent application CN202410672869.4 discloses a composite phase change material, a phase change temperature-adjustable lightweight ceramic tile and a preparation method thereof. The raw materials in this preparation process are mainly natural ores. Chinese invention patent CN202211273446.2 discloses a ceramic-based molten salt composite phase change heat storage material and a preparation method thereof. In this process, porous ceramics are prepared using steel slag and aluminum-rich silica ash as raw materials, which promotes the resource utilization of industrial solid waste. In the present invention, porous ceramics are prepared using industrial solid waste as raw materials, steel slag-based porous ceramics are prepared using waste wood pulp sponge and waste polyurethane sponge as templates, and steel slag-based porous ceramic composite phase change materials are further prepared. The present invention also promotes the resource utilization of industrial solid waste, biomass waste and plastic waste, reduces dependence on natural mineral resources, and contributes to environmental protection and reduction of carbon emissions.
[0006] In view of the above-mentioned defects, the inventors of the present invention finally obtained the present invention after a long period of research and practice. Summary of the invention
[0007] The purpose of the present invention is to solve the problems of high packaging cost, easy corrosion and leakage in the prior art of preparing composite phase change materials, and to alleviate the problem of low resource utilization rate of industrial solid waste, biomass waste and plastic waste, and to provide a steel slag-based porous ceramic composite phase change material and a preparation method thereof.
[0008] In order to achieve the above object, the present invention discloses a method for preparing a steel slag-based porous ceramic composite phase change material, comprising the following steps:
[0009] S1, soaking the polyurethane foam in sodium hydroxide solution and sodium carboxymethyl cellulose solution respectively, and then rinsing and drying to obtain the treated polyurethane foam;
[0010] S2, mixing steel slag, kaolin, boric acid, sodium dodecyl sulfate and alumina powder in proportion, then adding water and magnetically stirring to obtain slurry;
[0011] S3, soaking the treated polyurethane foam obtained in step S1 in mud, and vacuuming to completely absorb the mud into the polyurethane foam;
[0012] S4, scraping off excess mud on the surface of the polyurethane foam treated in step S3 with a spoon, and then aging it, and drying it after aging to obtain a polyurethane foam fully adsorbed with mud;
[0013] S5, placing the polyurethane foam that has absorbed the slurry in step S4 into a muffle furnace and sintering it to obtain a steel slag-based porous ceramic;
[0014] S6, vacuum-adsorbing the steel slag-based porous ceramic phase change material obtained in step S5 to obtain a steel slag-based composite phase change material.
[0015] In the step S1, the concentration of sodium hydroxide is 0.5-2 mol / L, the soaking time is 1-6 hours, the concentration of sodium carboxymethyl cellulose is 0.5-2%wt, and the soaking time is 1 hour.
[0016] In the step S1, the porosity of the polyurethane foam is in the range of 30 to 60 ppi, and the polyurethane foam can be replaced by wood pulp sponge or loofah.
[0017] In step S2, the masses of steel slag, kaolin, boric acid, sodium dodecyl sulfate, alumina powder and water are as follows: 2.8-3.2 g of steel slag, 2.3-3.2 g of kaolin, 0.8 g of boric acid, 0.15-0.75 g of sodium dodecyl sulfate, 0-0.3 g of alumina, and 4.0-5.0 g of water. Kaolin and steel slag can be replaced by fly ash, coal gangue, red mud, rice husk carbon or rice husk ash.
[0018] In step S2, the magnetic stirring time is 30 min.
[0019] In step S3, the vacuum degree of the vacuum drying oven is -0.1 to -0.05 MPa, and the vacuum adsorption time is 10 to 60 minutes.
[0020] In step S4, the slurry aging time is 24 to 48 hours, the drying temperature is 80 to 110° C., and the drying time is 10 to 24 hours.
[0021] In step S5, the sintering temperature of the muffle furnace is 700-1000° C., and the sintering time is 1-2 hours.
[0022] In the step S6, the phase change material is any one or more eutectic mixtures of paraffin, sodium sulfate decahydrate, sodium nitrate, and sodium chloride.
[0023] The invention also discloses a steel slag-based porous ceramic composite phase-change material prepared by the preparation method.
[0024] The key to the present invention is to use industrial solid wastes such as steel slag and fly ash as raw materials, biomass waste and plastic waste as templates, and adopt a foaming agent pore-forming method and a sacrificial template method to prepare porous ceramics. And by controlling the vacuum degree to adjust the filling degree of the mud in the porous template, the pore structure of the porous ceramic is improved, thereby improving the high adsorption rate of the porous ceramic to paraffin. The porous template provides a three-dimensional porous structure for the ceramic. The foaming agent further opens holes on the porous ceramic skeleton, thereby increasing the porosity of the porous ceramic. Partial filling of the mud under low vacuum further increases the pore volume of the porous ceramic. Finally, a solid waste-based porous ceramic composite phase change material with good thermal properties and thermal cycle properties is prepared using porous ceramics as a carrier.
[0025] Compared with the prior art, the beneficial effects of the present invention are:
[0026] 1. The steel slag-based porous ceramics prepared by the present invention have high porosity, high hardness and excellent stability. Using industrial solid wastes such as steel slag and fly ash as raw materials reduces dependence on natural ore materials and promotes the resource utilization of industrial solid wastes. In addition, using wood pulp sponge and polyurethane foam as templates promotes the resource utilization of biomass waste and plastic waste. The resource utilization of waste reduces the harm it may cause to the environment;
[0027] 2. The pore-forming method using a foaming agent plus a sacrificial template method is combined with the volatile components in the steel slag to form pores. The prepared steel slag-based porous ceramics have a rich pore structure and a high loading rate for phase change materials. The loading rate for paraffin can reach more than 50%. In addition, in the process of preparing porous ceramics by the sacrificial template method, vacuum adsorption impregnation is used to simplify the mud impregnation process, which can be suitable for large-scale production. By controlling the vacuum degree and adjusting the filling rate of the mud in the porous template, the porosity of the steel slag-based porous ceramics is increased, and the adsorption rate of the porous ceramics for phase change materials is increased;
[0028] 3. Steel slag-based ceramics and phase change materials have good chemical compatibility. The rich pore structure inside steel slag-based porous ceramics can load a large amount of phase change materials, and effectively prevent leakage of phase change materials after melting, thereby improving the safety and durability of phase change materials during application. Therefore, the composite phase change material prepared with steel slag-based ceramics as a carrier has good thermal properties and thermal cycle performance. At the same time, steel slag porous ceramics as a carrier have significant cost advantages over other carbon-based materials and metal materials. Carbon-based materials are not suitable for use at high temperatures, and the molten salt of metal materials is corroded by inorganic phase change materials. Steel slag-based porous ceramics have excellent high temperature resistance and corrosion resistance, and can load a variety of phase change materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 A preparation process of a steel slag-based porous ceramic and a steel slag-based porous ceramic composite phase change material of the present invention;
[0030] Figure 2 This is a physical picture of steel slag-based porous ceramics;
[0031] Figure 3 is the loading rate of paraffin wax in steel slag based porous ceramic composite phase change material;
[0032] Figure 4 It is the phase change latent heat of steel slag based porous ceramic composite phase change material. DETAILED DESCRIPTION
[0033] The above and other technical features and advantages of the present invention are described in more detail below in conjunction with the accompanying drawings.
[0034] Example 1
[0035] S1, soaking the wood pulp sponge in 1 mol / L sodium hydroxide solution and 1% (wt) sodium carboxymethyl cellulose solution, and then rinsing and drying the polyurethane foam 2;
[0036] S2, steel slag, kaolin, boric acid, sodium dodecyl sulfate and water were mixed in a ratio of 3.2:2.3:0.8:0.6:4.4, and magnetically stirred for 30 min to obtain a slurry;
[0037] S3, soaking the dried polyurethane foam 2 in the mud, vacuuming the mud to completely absorb it into the polyurethane foam 2, the vacuum degree is -0.1MPa, and the vacuum time is 30min;
[0038] S4, scraping the excess mud on the surface of the polyurethane with a spoon, then aging for 24 hours, and drying at 80°C for 24 hours after aging to obtain a polyurethane foam 3 fully adsorbed with mud;
[0039] S5, placing the polyurethane foam 3 after absorbing the slurry into a muffle furnace, sintering at 700° C. for 60 min to obtain steel slag-based porous ceramics;
[0040] S6, steel slag-based porous ceramics vacuum adsorb paraffin to obtain steel slag-based composite phase change materials, vacuum degree -0.1MPa, vacuum time 1h.
[0041] Example 2
[0042] S1, soaking the wood pulp sponge in 1 mol / L sodium hydroxide solution and 1% (wt) sodium carboxymethyl cellulose solution, and then rinsing and drying the polyurethane foam 2;
[0043] S2, mixing steel slag, fly ash, boric acid, sodium dodecyl sulfate and water in a ratio of 3.0:3.0:0.8:0.3:5.0, and magnetically stirring for 30 min to obtain slurry;
[0044] S3, soaking the dried polyurethane foam 2 in the mud, vacuuming the mud to completely absorb it into the polyurethane foam 2, the vacuum degree is -0.1MPa, and the vacuum time is 30min;
[0045] S4, scraping the excess mud on the surface of the polyurethane with a spoon, then aging for 24 hours, and drying at 80°C for 24 hours after aging to obtain a polyurethane foam 3 fully adsorbed with mud;
[0046] S5, placing the polyurethane foam 3 after absorbing the slurry into a muffle furnace, sintering at 700° C. for 60 min to obtain steel slag-based porous ceramics;
[0047] S6, steel slag-based porous ceramics vacuum adsorb paraffin to obtain steel slag-based composite phase change materials, vacuum degree -0.1MPa, vacuum time 1h.
[0048] Example 3
[0049] S1, soaking 60 ppi polyurethane foam in 1 mol / L sodium hydroxide solution and 1% (wt) sodium carboxymethyl cellulose solution, and then rinsing and drying polyurethane foam 2;
[0050] S2, steel slag, kaolin, boric acid, sodium dodecyl sulfate, alumina powder and water were mixed in a ratio of 3.2:2.3:2.0:3.0:4.4, and magnetically stirred for 30 min to obtain a slurry;
[0051] S3, soaking the dried polyurethane foam 2 in the mud, vacuuming the mud to completely absorb it into the polyurethane foam 2, the vacuum degree is -0.05MPa, and the vacuum time is 30min;
[0052] S4, scraping the excess mud on the surface of the polyurethane with a spoon, then aging for 24 hours, and drying at 80°C for 24 hours after aging to obtain a polyurethane foam 3 fully adsorbed with mud;
[0053] S5, placing the polyurethane foam 3 after absorbing the slurry into a muffle furnace, sintering at 700° C. for 60 min to obtain steel slag-based porous ceramics;
[0054] S6, steel slag-based porous ceramics vacuum adsorb paraffin to obtain steel slag-based composite phase change material, vacuum degree -0.05MPa, vacuum time 1h.
[0055] Example 4
[0056] S1, soaking the wood pulp sponge in 1 mol / L sodium hydroxide solution and 1% (wt) sodium carboxymethyl cellulose solution, and then rinsing and drying the wood pulp sponge 2;
[0057] S2, mixing steel slag, fly ash, boric acid, sodium dodecyl sulfate and water in a ratio of 3.0:3.0:0.8:0.45:5.0, and magnetically stirring for 30 min to obtain slurry;
[0058] S3, soaking the dried wood pulp sponge 2 in the mud, and vacuuming the mud to completely absorb it into the wood pulp sponge 2, the vacuum degree is -0.1MPa, and the vacuum time is 30min;
[0059] S4, scraping the excess mud on the surface of the polyurethane with a spoon, then aging for 24 hours, and drying at 80°C for 24 hours after aging to obtain a polyurethane foam 3 fully adsorbed with mud;
[0060] S5, placing the polyurethane foam 3 after absorbing the slurry into a muffle furnace, sintering at 700° C. for 60 min to obtain steel slag-based porous ceramics;
[0061] S6, steel slag-based porous ceramics vacuum adsorb paraffin to obtain steel slag-based composite phase change materials, vacuum degree -0.1MPa, vacuum time 1h.
[0062] Example 5
[0063] S1, soaking the wood pulp sponge in 1 mol / L sodium hydroxide solution and 1% (wt) sodium carboxymethyl cellulose solution, and then rinsing and drying the wood pulp sponge 2;
[0064] S2, mixing steel slag, fly ash, boric acid, sodium dodecyl sulfate and water in a ratio of 3.0:3.0:0.8:0.45:5.0, and magnetically stirring for 30 min to obtain slurry;
[0065] S3, soaking the dried wood pulp sponge 2 in the mud, and vacuuming the mud to completely absorb it into the wood pulp sponge 2, the vacuum degree is -0.1MPa, and the vacuum time is 30min;
[0066] S4, scraping the excess mud on the surface of the polyurethane with a spoon, then aging for 24 hours, and drying at 80°C for 24 hours after aging to obtain a polyurethane foam 3 fully adsorbed with mud;
[0067] S5, placing the polyurethane foam 3 after absorbing the slurry into a muffle furnace, sintering at 700° C. for 60 min to obtain steel slag-based porous ceramics;
[0068] S6, steel slag-based porous ceramic vacuum adsorbs paraffin to obtain steel slag-based composite phase change material, vacuum degree -0.1MPa, vacuum time 1h,
[0069] S7, testing the thermal cycling performance of the sample. The steel slag-based composite phase change material was kept at 100°C and 20°C for 5 minutes respectively, for a total of 50 cycles.
[0070] Comparative Example 1
[0071] This comparative example is mainly used as a blank control for Example 1 and comprises the following steps:
[0072] A pure paraffin phase change material is used as a comparative example.
[0073] Comparative Example 2
[0074] This comparative example is mainly used as a blank control for Example 1 and comprises the following steps:
[0075] Steel slag was used as a carrier and paraffin was vacuum adsorbed to obtain a steel slag-based composite phase change material with a vacuum degree of -0.1 MPa and a vacuum time of 1 h.
[0076] Comparative Example 3
[0077] S1, soaking 30 ppi polyurethane foam in 1 mol / L sodium hydroxide solution and 1% (wt) sodium carboxymethyl cellulose solution, and then rinsing and drying polyurethane foam 2;
[0078] S2, steel slag, kaolin, boric acid, sodium dodecyl sulfate and water were mixed in a ratio of 3.2:2.3:0.2:0.3:4.4, and magnetically stirred for 30 min to obtain a slurry;
[0079] S3, soaking the dried polyurethane foam 2 in the mud, vacuuming the mud to completely absorb it into the polyurethane foam 2, the vacuum degree is -0.05MPa, and the vacuum time is 30min;
[0080] S4, scraping the excess mud on the surface of the polyurethane with a spoon, then aging for 24 hours, and drying at 80°C for 24 hours after aging to obtain a polyurethane foam 3 fully adsorbed with mud;
[0081] S5, placing the polyurethane foam 3 after absorbing the slurry into a muffle furnace, sintering at 700° C. for 60 min to obtain steel slag-based porous ceramics;
[0082] S6, steel slag-based porous ceramics vacuum adsorb paraffin to obtain steel slag-based composite phase change materials, vacuum degree -0.1MPa, vacuum time 1h.
[0083] Comparative Example 4
[0084] S1, soaking 60 ppi polyurethane foam in 1 mol / L sodium hydroxide solution and 1% (wt) sodium carboxymethyl cellulose solution, and then rinsing and drying polyurethane foam 2;
[0085] S2, steel slag, kaolin, boric acid, sodium dodecyl sulfate, alumina powder and water were mixed in a ratio of 3.2:2.3:0.8:0.3:4.4, and magnetically stirred for 30 min to obtain a slurry;
[0086] S3, soaking the dried polyurethane foam 2 in the mud, vacuuming the mud to completely absorb it into the polyurethane foam 2, the vacuum degree is -0.1MPa, and the vacuum time is 30min;
[0087] S4, scraping the excess mud on the surface of the polyurethane with a spoon, then aging for 24 hours, and drying at 80°C for 24 hours after aging to obtain a polyurethane foam 3 fully adsorbed with mud;
[0088] S5, placing the polyurethane foam 3 after absorbing the slurry into a muffle furnace, sintering at 700° C. for 60 min to obtain steel slag-based porous ceramics;
[0089] S6, steel slag-based porous ceramics vacuum adsorb paraffin to obtain steel slag-based composite phase change materials, vacuum degree -0.1MPa, vacuum time 1h.
[0090] like Figure 2 As shown, the surface of the porous ceramic in Comparative Example 4 is relatively dense and has no obvious pore structure. Compared with Comparative Example 4, Example 1 uses wood pulp sponge as a porous template, and the prepared porous ceramic has a rich pore structure. Example 3 uses mud to partially fill the porous material, and the prepared porous ceramic has a larger volume. In Example 4, a sacrificial template method plus a foaming agent pore-forming process is used. Under the action of the foaming agent, the porous ceramic has an obvious loose pore structure.
[0091] like Figure 3As shown, in Example 1, compared with Comparative Example 1, after steel slag is prepared into porous ceramics, its loading rate in the phase change material is significantly improved. In Example 2, compared with Example 1, kaolin in the raw materials is replaced with fly ash, an industrial solid waste. After adding fly ash, the adsorption performance of porous ceramics is improved and promoted. Comparing Example 3 with Comparative Example 3, the results show that the porosity of polyurethane foam has a significant effect on the adsorption performance of porous ceramics. Porous ceramics prepared with high porosity polyurethane foam have better adsorption performance. Comparison results of Example 4 and Comparative Example 4 show that the filling rate of mud to the porous template is different under different vacuum degrees. The vacuum degree in Example 4 is lower than that in Comparative Example 4, so the mud filling degree in Example 4 is lower. It shows that partial filling of mud in the porous template is more conducive to the preparation of porous ceramics with high adsorption rate.
[0092] like Figure 4 As shown, comparative example 1 is the latent heat parameter of pure paraffin. Example 1 and Example 2 have higher adsorption rates than comparative example 2, and therefore have higher latent heat. Example 5 is the parameter of Example 4 after 50 thermal cycles. After multiple thermal cycles, Example 5 still has good thermal performance, indicating that the prepared steel slag-based composite phase change material has good thermal cycle performance.
[0093] The above description is only a preferred embodiment of the present invention, which is only illustrative and not restrictive of the present invention. Those skilled in the art understand that many changes, modifications, and even equivalences may be made to the present invention within the spirit and scope defined by the claims of the present invention, but all of them will fall within the scope of protection of the present invention.
Claims
1. A method for preparing a steel slag-based porous ceramic composite phase change material, characterized in that: The following steps are involved: S1, soaking the polyurethane foam in sodium hydroxide solution and sodium carboxymethyl cellulose solution respectively, and then rinsing and drying to obtain the treated polyurethane foam; S2, mixing steel slag, kaolin, boric acid, sodium dodecyl sulfate and alumina powder in proportion, then adding water and stirring with a magnetic force to obtain slurry; S3, soaking the treated polyurethane foam obtained in step S1 in mud, and vacuuming to completely absorb the mud into the polyurethane foam; S4, scraping off excess mud on the surface of the polyurethane foam treated in step S3 with a spoon, and then aging it, and drying it after aging to obtain a polyurethane foam fully adsorbed with mud; S5, placing the polyurethane foam that has absorbed the slurry in step S4 into a muffle furnace and sintering it to obtain a steel slag-based porous ceramic; S6, vacuum-adsorbing the steel slag-based porous ceramic phase change material obtained in step S5 to obtain a steel slag-based composite phase change material.
2. The method for preparing a steel slag-based porous ceramic composite phase change material according to claim 1, characterized in that: In the step S1, the concentration of sodium hydroxide is 0.5-2 mol / L, the soaking time is 1-6 hours, the concentration of sodium carboxymethyl cellulose is 0.5-2%wt, and the soaking time is 1 hour.
3. The method for preparing a steel slag-based porous ceramic composite phase change material according to claim 1, characterized in that: In the step S1, the porosity of the polyurethane foam is in the range of 30 to 60 ppi, and the polyurethane foam can be replaced by wood pulp sponge or loofah.
4. The method for preparing a steel slag-based porous ceramic composite phase change material according to claim 1, characterized in that: In step S2, the masses of steel slag, kaolin, boric acid, sodium dodecyl sulfate, alumina powder and water are as follows: 2.8-3.2 g of steel slag, 2.3-3.2 g of kaolin, 0.8 g of boric acid, 0.3-0.75 g of sodium dodecyl sulfate, 0-0.3 g of alumina, and 4.0-5.0 g of water. Kaolin and steel slag can be replaced by fly ash, coal gangue, red mud, rice husk carbon or rice husk ash.
5. The method for preparing a steel slag-based porous ceramic composite phase change material according to claim 1, characterized in that: In step S2, the magnetic stirring time is 30 min.
6. The method for preparing a steel slag-based porous ceramic composite phase change material according to claim 1, characterized in that: In step S3, the vacuum degree of the vacuum drying oven is -0.1 to -0.05 MPa, and the vacuum adsorption time is 10 to 60 minutes.
7. The method for preparing a steel slag-based porous ceramic composite phase change material according to claim 1, characterized in that: In step S4, the slurry aging time is 24 to 48 hours, the drying temperature is 80 to 110° C., and the drying time is 10 to 24 hours.
8. The method for preparing a steel slag-based porous ceramic composite phase change material according to claim 1, characterized in that: In step S5, the sintering temperature of the muffle furnace is 700-1000° C., and the sintering time is 1-2 hours.
9. The method for preparing a steel slag-based porous ceramic composite phase change material according to claim 1, characterized in that: In the step S6, the phase change material is any one or more eutectic mixtures of paraffin, sodium sulfate decahydrate, sodium nitrate, and sodium chloride.
10. A steel slag-based porous ceramic composite phase change material prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Composite phase-change material, phase-change temperature-adjusting lightweight ceramic tile and preparation method of phase-change temperature-adjusting lightweight ceramic tile
CN118620580A
Three-dimensional reticulated spinel-cordierite porous ceramic with high porosity and preparation method thereof
CN110423099A
Porous phase change energy storage material prepared from mine solid waste and method
CN114890811A
Ceramic-based fused salt composite phase change heat storage material and preparation method thereof
CN115432997A
Method for preparing porous TaC ceramic by using organic foam template method
CN118652120A
Cited By
Steel slag-based composite phase change heat storage material as well as preparation method and application thereof
CN122059718A
A steel slag-based composite phase change thermal energy storage material, its preparation method and application
CN122059718B